A 50-Year-Old Female with Duplex Collecting System Following The Weigert-Meyer Rule - Deta Anggreawan Rengga (JOSING: Journal of Nursing and Health, 2026)
This study aims to describe the clinical presentation, radiological features, and management of a case of duplex collection system diagnosed in adulthood. Methods This study used a case report method. Data were obtained through anamnesis, physical examination, supporting examinations in the form of abdominal ultrasonography (USG) and Multislice Computed Tomography (MSCT), as well as intraoperative findings and patient medical records. Data were analyzed descriptively by comparing the examination results with relevant literature. The results of the USG examination showed lesions in the left hemiabdomen and pelvic cavity with a differential diagnosis of hydronephrosis, hydropyonephrosis, left hydroureter, colonic mass, and left ectopic kidney. Abdominal MSCT examination confirmed the presence of a dual collecting system in the left kidney with grade IV hydronephrosis in the upper pole collecting system that empties into the ureterocele according to the Weigert-Meyer Rule. Surgery revealed severe hydronephrosis in the upper pole of the left kidney accompanied by left hydroureter. In conclusion, a dual collecting system (DCS) is a rare congenital anomaly typically diagnosed in childhood, but in some cases it can remain asymptomatic into adulthood. Radiological examination, particularly abdominal CT scan, plays a crucial role in establishing the diagnosis and determining appropriate management.   Keywords: Dual Collecting System, Hydronephrosis, Weigert-Meyer Rule, Ureterocele, Adults